Nanocellulose as promising reinforcement materials for biopolymer nanocomposites: a review - Tung, Ngo Trinh; Y Nhi, Tran Thi; Cong, Trinh Duc; Thanh Hop, Tran Thi; Mai, Dang Thi (Vietnam Journal of Science and Technology, 2024)
Abstract. A green and sustainable development in world is important and it needs to further strengthen at the moment. In this aspect, biopolymers, biopolymers nanocomposites with biodegradable properties are the best way for this purpose. Nanocellulose (NC) is a biopolymer and can be produced from natural resources like various plant species and agricultural waste products including rice husk, tea leaves, sugarcane bagasse and so forth. Due to their special properties such as biodegradability, renewability, biocompability, low cost and outstanding mechanical capabilities, NC have gained increased research and application interests. This review provided detail information about the production, structure and properties of NC. The usage of NC as reinforcement materials for different types of biopolymers are presented in the review. The surface modification of NC for better dispersion and better interaction of NCs in polymer matrices, the mechanical and thermal properties of the NC biopolymers nanocomposites are discussed.